Effectiveness of multiple-dose activated charcoal in lamotrigine poisoning: a case series. (4th March 2022) - Hatanaka, Kengo; Kamijo, Yoshito; Kitamoto, Takeshi; Hanazawa, Tomoki; Yoshizawa, Tomohiro; Ochiai, Hidenobu; Haga, Yoshiyuki
Abstract: Introduction: Lamotrigine toxicity can cause coma, seizures, and intraventricular conduction disturbances, and treatment options include good supportive care. We report two cases of lamotrigine poisoning in which multiple-dose activated charcoal may have shortened the elimination half-life of lamotrigine. Case 1: A 21-year-old woman ingested 15.6 g lamotrigine, 14 g levetiracetam, and 15 mg clonazepam. She became comatose and developed generalized tonic seizure. One hour post-ingestion, 50 g activated charcoal was administered. Starting 11 h post-ingestion, 25 g activated charcoal was administered every 4 h for 4 doses. The peak concentration of serum lamotrigine was 49.5 µg/mL, and the elimination half-life after commencement of multiple-dose activated charcoal was 6.5 h. Case 2: A 46-year-old woman ingested 0.3 g lamotrigine and 0.1 g topiramate twice, 2 h apart. She became drowsy, complained of blurred vision, vertigo, nausea, and vomited. An initial dose of 50 g activated charcoal was administered at 4.5 h post-second ingestion, and subsequent doses of 25 g (total of 3 doses) were administered every 4 h, commencing at 8.5 h post-second ingestion. The peak concentration of serum lamotrigine was 19.9 µg/mL, and the elimination half-life after commencement of multiple-dose activated charcoal was 9.3 h. Discussion: The mean elimination half-life of lamotrigine in healthy volunteers and epileptic patients receiving lamotrigine monotherapy is 22.8–37.4 h. In our two cases, multiple-dose activated charcoal may have shortened the elimination half-life of lamotrigine, possibly by inhibiting enterohepatic circulation. Multiple-dose activated charcoal should be considered an option for treating lamotrigine poisoning.